Polity and Ecology in Formative Period Coastal Oaxaca - ARTHUR A. JOYCE (University Press of Colorado, 2013)
In the early 1960s Richard MacNeish designed a groundbreaking regional archaeological study focused on Mexico’s Tehuacán Valley. Enlisting the collaboration of specialists in paleobotany, zoology, geology, geography, hydrology, lithic technology, ethnography, and ethnohistory, MacNeish and his colleagues applied the results of their Tehuacán field and laboratory research to a processual-ecological model through which they fashioned a wide-ranging reconstruction of sociocultural evolution in that arid highland valley. Beginning with the arrival of nomadic hunter-gatherers, their story continued through the development of agriculture, settled village life, and increasing sociopolitical complexity, right up to the time of the sixteenth- century Spanish conquest of indigenous Mexico. The enduring legacy of MacNeish’s Tehuacán project lies not only in its compelling demonstration of the value of interdisciplinary research but as an example of the importance of studies in hinterland regions at a time when much archaeological attention was focused on the more spectacular centers of high pre-Columbian civilization. A half century later, Art Joyce and his colleagues continue in that interdisciplinary tradition with their study Polity and Ecology in Formative Period Coastal Oaxaca. Building upon the region’s earliest archaeological research by Donald Brockington, to whom this volume is dedicated, Joyce has gathered a group of researchers to employ their diverse expertise toward a comprehensive reconstruction of Formative period archaeological and paleoecological developments in this underappreciated Pacific coastal region of Mesoamerica.